The blue carbon of southern southwest Atlantic salt marshes and their biotic and abiotic drivers - Martinetto, Paulina Maria del Rosario (2023)
Coastal vegetated ecosystems are acknowledged for their capacity to sequester organic carbon (OC), known as blue C. Yet, blue C global accounting is incomplete, with major gaps in southern hemisphere data. It also shows a large variability suggesting that the interaction between environmental and biological drivers is important at the local scale. In southwest Atlantic salt marshes, to account for the space occupied by crab burrows, it is key to avoid overestimates. Here we found that southern southwest Atlantic salt marshes store on average 42.43 (SE = 27.56) Mg OC·ha−1 (40.74 (SE = 2.7) in belowground) and bury in average 47.62 g OC·m−2·yr−1 (ranging from 7.38 to 204.21). Accretion rates, granulometry, plant species and burrowing crabs were identified as the main factors in determining belowground OC stocks. These data lead to an updated global estimation for stocks in salt marshes of 185.89 Mg OC·ha−1 (n = 743; SE = 4.92) and a C burial rate of 199.61 g OC·m−2·yr−1 (n = 193; SE = 16.04), which are lower than previous estimates.